Spatial Variability of the Feeding Conditions for the Norwegian Spring Spawning Herring in May - Kristiansen, Inga; Hátún, Hjálmar; Jacobsen, Jan Arge; Eliasen, Sólvá K.; Petursdottir, Hildur; Gaard, Eilif (Frontiers in Marine Science, 2022)
The abundant and ecologically important copepods Calanus finmarchicus and Calanus hyperboreus within the Norwegian and Iceland Seas are key prey species of Norwegian spring spawning herring. The volume flux of East Icelandic Water, which carries the mentioned zooplankton species into the southern Norwegian Sea, is highly variable. The years 1996–2002 have previously been characterized as high influx years, 2003–2016 as low influx years and since 2017 a reversal to higher influx has been apparent. Hydrographic and zooplankton data, as well as fish data on herring (size and diet content), from the International Ecosystem Surveys in the Nordic Seas in May have been used in this study. Focus is on the south-western Norwegian Sea, where herring has regularly been observed in May since 2005 and where changes in plankton availability and in the hydrographic environment have also been observed. Diet biomass from 2017–2020 (higher influx period) showed higher stomach fullness compared to 2007–2011 (lower influx period). Furthermore, the highest stomach fullness is observed in the westernmost feeding region—referred to as the Feeding Spot. The scrutinized diet content showed a notably higher biomass of ingested C. hyperboreus in 2020 compared to 2007–2011, indicating a preference for the larger and more nutritious copepod. Zooplankton analysis from May 2020 revealed that the core of the western feeding region, i.e., the area with highest zooplankton biomass, was located within the subarctic waters immediately north/west of the junction between the Iceland-Faroe Front and the Jan Mayen Front. The core area was mainly represented by overwintering stages and the derived adult stages of C. finmarchicus and C. hyperboreus. Interplay between food availability and accessibility, in terms of temperature, to the Feeding Spot, is discussed.